Diagnostic and therapeutic challenges in colonic eosinophilic abscess complicated with eosinophilic vasculitis: a case report and literature review - Ding, Na; Zhao, Jianru; Tian, Feng; Li, Hui (Frontiers in Medicine, 2025)
This case report and literature review present a 52-year-old male with a sigmoid eosinophilic abscess (EA) complicated by eosinophilic vasculitis (EoV), resulting in thrombosis and intestinal perforation. The patient presented with acute abdominal pain and melena. Laboratory tests revealed marked eosinophilia, elevated D-dimer levels, and a white blood cell count consistent with systemic inflammation. Contrast-enhanced computed tomography (CECT) identified extensive vascular thrombosis and bowel wall compromise, necessitating surgical intervention. Histopathological examination confirmed the diagnosis of EA with associated eosinophilic infiltration in the intestinal wall. This case highlights the diagnostic and therapeutic challenges of eosinophilic disorders, particularly the need for awareness of their potential complications. It also emphasizes the importance of timely intervention in managing such rare conditions. Through a review of the relevant literature, we further discuss the characteristics, differential diagnosis, and management strategies for EA and EoV.